SUBTITUSI TEPUNG TERIGU DENGAN TEPUNG MAIZENA PADA PEMBUATAN PASTA - Netty Duma; Rosniati Rosniati (Jurnal Dinamika Penelitian Industri, 2010)
Pasta is a kind of food made from wheat flour, water and other additional ingredients. This research was aimed to know the impact of wheat flour substitution with maize flour in pasta making. Preliminary research was done to found the better formulate between CMC, STPP, wheat flour and maize flour in pasta making and resulted good formula between wheat flour ad maize flour were 90% : 10%: 80%: 20%: and 70%: 30%. These formulate were used for the main research and the best formulated were resulted on 90% wheat flour and 10% maize flour water content was 9,10% which near to control value 8,14%. Rehydration potential was 9,93 minute and elasticity value 792,4 N/m2 which almost similar the elasticity control value 810,73N/m2.